2019
DOI: 10.1071/ah18062
|View full text |Cite
|
Sign up to set email alerts
|

Transforming institutional racism at an Australian hospital

Abstract: Objectives The aims of this study were to: (1) examine institutional racism’s role in creating health outcome discrepancies for Aboriginal and Torres Strait Islander peoples; and (2) assess the management of institutional racism in an Australian hospital and health service (HHS). Methods A literature review informed consideration of institutional racism and the health outcome disparities it produces. Publicly available information, provided by an Australian HHS, was used to assess change in an Australian HHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…The complete absence of Aboriginal people from population-wide national food and nutrition committees over a 10 year policy trajectory affirms the Australian norm of 'legal invisibility' of Aboriginal people in Australian policy-making, and recreates institutional inequity in policy responses. 54 We found that the vast majority of submissions in population-wide food and nutrition policy processes were from non-Aboriginal organisations. Along with the membership of oversight committees consisting of non-Aboriginal experts, civil servants and politicians, and the control of the policy process by governments, politicians and government statutory organisations, this indicates the dominance of non-Aboriginal voices in the legitimation of knowledge, decisions about who makes the rules and where resources are allocated.…”
Section: Cultural Safetymentioning
confidence: 84%
“…The complete absence of Aboriginal people from population-wide national food and nutrition committees over a 10 year policy trajectory affirms the Australian norm of 'legal invisibility' of Aboriginal people in Australian policy-making, and recreates institutional inequity in policy responses. 54 We found that the vast majority of submissions in population-wide food and nutrition policy processes were from non-Aboriginal organisations. Along with the membership of oversight committees consisting of non-Aboriginal experts, civil servants and politicians, and the control of the policy process by governments, politicians and government statutory organisations, this indicates the dominance of non-Aboriginal voices in the legitimation of knowledge, decisions about who makes the rules and where resources are allocated.…”
Section: Cultural Safetymentioning
confidence: 84%
“…DAMA is considered an indirect measure of the cultural competency of health care services and, in the case of Aboriginal Australians, may reflect suboptimal responsiveness of hospitals to Aboriginal needs and poorer quality of care [13]. This has been well-documented in Australian hospitals and has been termed “institutional racism”, [26]. The provision of culturally appropriate care for Aboriginal patients is directly linked to health outcomes [27].…”
Section: Discussionmentioning
confidence: 99%
“…There is a widely held argument among researchers and practitioners that the socio-economic circumstances and political underrepresentation of minority groups point to ongoing systematic and structural racial inequality and injustice (Larkin 2013 ). Whether these are indicative of an underlying institutional racism, with race/ethnicity still determining one’s place in Australian society, is a heavily debated issue across public policy and academic discourse (Bourke, Marrie, and Marrie 2018 ; Fuller, Howard, and Cummings 2004 ; Mellor 2003 ).…”
Section: Institutional Racism In the Australian Contextmentioning
confidence: 99%
“…This is clearly seen in Australia, in the poor health outcomes of Aboriginal and Torres Strait Islanders, as consistently reported in the Closing the Gap report. According to this report, social determinants of health and risk factors accounted for 53 per cent of the health disparity between Indigenous and non-Indigenous Australians while interpersonal and institutional racism and related factors accounted for the remaining 47 per cent (Bourke, Marrie, and Marrie 2018 ). Institutional racism places a heavy burden on the Indigenous people and is perpetuated by their systematic exclusion from the healthcare system.…”
Section: The Cost Of Institutional Racismmentioning
confidence: 99%